Mechanical factors affecting the foot eversion moment during the stance phase of running in non-rearfoot strikers - Tsujimoto, N.; Nunome, H.; Mizuno, T.; Inoue, K.; Matsui, K.; Matsugi, R.; Ikegami, Y. (Sports Biomechanics, 2021)
This study aimed to identify the primary factors that induce rearfoot external eversion moments due to ground reaction force (GRF) in non-rearfoot strikers. The data were compared with those of rearfoot strikers. Totally, 11 healthy males who were habitually non-rearfoot strikers ran barefoot. Rearfoot external eversion/inversion moments due to GRF (Mtot) were decomposed into two components based on mediolateral (Mxy) and vertical (Mz) GRFs. The height of the ankle joint centre and the mediolateral distance from the centre of pressure (COP) to the ankle joint centre (a_cop) were calculated as the lever arms to the Mxy and Mz components. Just after foot contact, non-rearfoot strikers demonstrated a significantly larger Mz, which was strongly dependent on a_cop and produced most of the Mtot, whereas Mxy dominated Mtot in rearfoot strikers. During the consecutive loading phase, non-rearfoot strikers demonstrated a significantly larger Mxy, which was strongly dependent on the mediolateral GRF and substantially contributed to Mtot, unlike the rearfoot strikers, whose Mtot was almost dominated by Mz during the loading phase. It was found that since the factor of generating the moment differs depending on the foot contact pattern, the strategies for suppressing the moment may be different for each foot contact pattern.